2018
DOI: 10.1186/s40169-018-0183-8
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of ADSCs to HSC‐progenitors in adipose tissue derived SVF may provide the key to predict the outcome of stem‐cell therapy

Abstract: Background Stromal vascular fraction (SVF) represents an attractive source of adult stem cells and progenitors, holding great promise for numerous cell therapy approaches. In 2017, it was reported that 1524 patients received autologous SVF following the enzymatic digestion of liposuction fat. The treatment was safe and effective and patients showed significant clinical improvement. In a collaborative study, we analyzed SVF obtained from 58 patients having degenerative, inflammatory, autoimmune dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…The SVF fraction can be roughly divided into CD45 + cells, which contain the leukocytes, and CD45cells, comprising the ASCs, ECs, EPCs, etc. Although previous studies have indicated the efficacy of leukocytes in SVF employed in clinical treatments [Le et al, 2018], the focus of most clinical research has been to characterize the ASC-containing CD45cell fraction [Kilinc et al, 2018]. The live ASC cell population in the SVF was significantly reduced over time and declined with increasing temperatures, and the most prominent decrease was observed during storage at 37 ° C. Here, we report that storage significantly alters the SVF cell composition.…”
Section: Figure 2 Monocytesmentioning
confidence: 75%
“…The SVF fraction can be roughly divided into CD45 + cells, which contain the leukocytes, and CD45cells, comprising the ASCs, ECs, EPCs, etc. Although previous studies have indicated the efficacy of leukocytes in SVF employed in clinical treatments [Le et al, 2018], the focus of most clinical research has been to characterize the ASC-containing CD45cell fraction [Kilinc et al, 2018]. The live ASC cell population in the SVF was significantly reduced over time and declined with increasing temperatures, and the most prominent decrease was observed during storage at 37 ° C. Here, we report that storage significantly alters the SVF cell composition.…”
Section: Figure 2 Monocytesmentioning
confidence: 75%
“…ASCs attracted significantly more Lineage − Sca-1 + c-kit + cells to the BM in comparison with BM-MSCs. This supportive effect in hematopoietic recovery was a result of the dose-dependent effect of ASCs [31], but the effective ASC:HSC ratio differed among several research groups [31,32]. ASCs were also able to help hematopoietic reconstitution when they were directly The number of registered clinical trials is obtained from the website of the U.S. National Library of Medicine under the terms "adipose-derived stromal/stem cells" and "bone marrow mesenchymal stromal/stem cells" respectively (until September 2019)…”
Section: Hematopoiesis-regulating Properties Of Ascsmentioning
confidence: 99%
“…Patients received intraventricular SVF injection volumes of 3.5-20 cc (median: 4 cc) containing 4.05 × 10 5 to 6.2 × 10 7 cells/cc and contained on average 8% hematopoietic and 7.5% ADSCs by fluorescence-activated cell sorting (FACS) cytometry [11,45].…”
Section: Patientsmentioning
confidence: 99%